2013
DOI: 10.1128/jvi.01940-12
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Semliki Forest Virus Neurovirulence by MicroRNA-Mediated Detargeting

Abstract: cArtificial target sequences for tissue-specific miRNAs have recently been introduced as a new means for altering the tissue tropism of viral replication. This approach can be used to improve the safety of oncolytic viruses for cancer virotherapy by restricting their replication in unwanted tissues, such as the liver. Semliki Forest virus (SFV) is a positive-strand RNA virus and, similar to the related alphaviruses, like Sindbis virus, has potential as a gene therapy vector and an oncolytic virotherapy agent, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
63
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 34 publications
2
63
0
Order By: Relevance
“…2B, G-J). This finding is in accordance with previous reports, where miRT124 attenuated SFV4 was used (20) and confirms that IFNb secretion depends on the efficiency of virus replication in the brain (38).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…2B, G-J). This finding is in accordance with previous reports, where miRT124 attenuated SFV4 was used (20) and confirms that IFNb secretion depends on the efficiency of virus replication in the brain (38).…”
Section: Discussionsupporting
confidence: 82%
“…Previously, miRT124-tagged SFV4 was shown to possess significantly reduced neurovirulence (16,20). But, a few mice still developed severe neurological symptoms, with virus replication detected in the oligodendrocytes of corpus callosum and spine (16,20). The triple miRT de-targeted SFV4 virus (SFV4miRT) presented herein had attenuated replication in mouse brain cells specifically neurons, and oligodendrocytes (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the neurotoxicity of virulent alphaviruses precludes use of them as oncolytic agents. In this regard, we previously demonstrated that the replication of virulent SFV4 in neurons can be inhibited by inserting into the viral nonstructural genome multiple target sequences for the micro-RNA (miRNA) miR-124 (SFV4-miRT124) (17). On the other hand, the miR-124 target sites do not interfere with the expression of viral genes in cells lacking miR-T124 expression (17), notably gliomas (18).…”
mentioning
confidence: 99%